Odpowiedzi

2010-03-22T20:07:44+01:00
A) 2x2 + 1 = 9 - 2x2
4 + 1 = 9 - 4
5=5
TAK
b) 3(2x1 1/2 - 5)= 1 - 4x1 1/2
9-15= 1- 6
-6=-5
NIE
c) 4(y-6)-3y=2(y-9)
4(6-6)-3x6=2(6-9)
24-24-18=12-18
-18=-6
NIE
13 3 13
2010-03-22T20:10:17+01:00
A) 2x +1 = 9 - 2x, 2
4+1=9-4
5=5 spełnia


b) 3(2x - 5) = 1 - 4x, 1 1/2
3(2*3/2 - 5)=1-4*3/2
3(3-5)=1-6
3*(-2)=-5
-6=-5 nie spełnia

c) 4(y - 6) - 3y = 2(y - 9), 6
4*0-18=2*(-3)
-18=-6 nie spełnia
12 3 12
2010-03-22T20:14:10+01:00
A) 2x+1=9-2x
2x+2x=9-1
4x=8
x=2
Odp. Spełnia

b) 3(2x-5)=1-4x
6x-15=1-4x
6x+4x=15+1
10x=16
x=1,6
Odp. Nie spełnia

c) 4(y-6)-3y=2(y-9)
4y-24-3y=2y-18
4y-3y-2y=24-18
-1y=6
y=-6
Odp. Nie spełnia
4 3 4